Effects of Running on Sand vs. Stable Ground on Kinetics and Muscle Activities in Individuals With Over-Pronated Feet - Jafarnezhadgero, AmirAli; Amirzadeh, Nasrin; Fatollahi, Amir; Siahkouhian, Marefat; Oliveira, Anderson S.; Granacher, Urs (Frontiers in Physiology, 2022)
Background: In terms of physiological and biomechanical characteristics, over-pronation of the feet has been associated with distinct muscle recruitment patterns and ground reaction forces during running. Objective: The aim of this study was to evaluate the effects of running on sand versus stable ground on ground-reaction-forces (GRFs) and electromyographic (EMG) activity of lower limb muscles in individuals with over-pronated feet (OPF) compared with healthy controls. Methods: Thirty-three OPF individuals and 33 controls ran at preferred speed and in randomized-order over level-ground and sand. A force-plate was embedded in an 18-m runway to collect GRFs. Muscle activities were recorded using an EMG-system. Data were adjusted for surface-related differences in running speed. Results: Running on sand resulted in lower speed compared with stable ground running (p<0.001; d=0.83). Results demonstrated that running on sand produced higher tibialis anterior activity (p=0.024; d=0.28). Also, findings indicated larger loading rates (p=0.004; d=0.72) and greater vastus medialis (p<0.001; d=0.89) and rectus femoris (p=0.001; d=0.61) activities in OPF individuals. Controls but not OPF showed significantly lower gluteus-medius activity (p=0.022; d=0.63) when running on sand. Conclusions: Running on sand resulted in lower running speed and higher tibialis anterior activity during the loading phase. This may indicate alterations in neuromuscular demands in the distal part of the lower limbs when running on sand. In OPF individuals, higher loading rates together with greater quadriceps activity may constitute a proximal compensatory mechanism for distal surface instability.